1992
DOI: 10.1089/thy.1992.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexamethasone, Calcium and 1,25-Dihydroxycholecalciferol on Calcitonin and Calcitonin Gene-Related Peptide mRNA Levels from the CA-77 C Cell Line

Abstract: We used the CA-77 cell, a murine C-cell line derived from a medullary thyroid carcinoma, to study the effects of glucocorticoids, calcium, and vitamin D metabolites on calcitonin (CT) gene expression. Total RNA was isolated, and CT and CT gene-related peptide (CGRP) mRNAs were measured by Northern hybridizations using specific probes. A control mRNA probe (cyclophilin) was used to quantitate the specificity of the changes in CT and CGRP mRNAs. The CA-77 C cell line cultured in basal conditions with a medium de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The dose of 17(3-estradiol used in the present in vitro studies (100 nmol/I) was shown to achieve a maximal increase of CT secretion by thyroparathyroid gland complexes of 8-d-old rat pups (Greenberg et al, 1986) (Naveh-Many et al, 1992), and also with the fact that estradiol given to ovariectomized animals prevents the decrease in CT mRNA levels (Naveh-Many et al, 1992;Lamari et al, 1994 (Russo et al, 1988;Collignon et al, 1992) and enhances the biosynthesis and release of both CT and CGRP (Lamari et al, 1994) in CA-77 C cells has already been reported. All-trans-retinoic acid also was shown to decrease both CT and CGRP mRNAs in CA-77 C cells and the secretion of both peptides (Lamari et al, 1994).…”
Section: Discussionmentioning
confidence: 71%
“…The dose of 17(3-estradiol used in the present in vitro studies (100 nmol/I) was shown to achieve a maximal increase of CT secretion by thyroparathyroid gland complexes of 8-d-old rat pups (Greenberg et al, 1986) (Naveh-Many et al, 1992), and also with the fact that estradiol given to ovariectomized animals prevents the decrease in CT mRNA levels (Naveh-Many et al, 1992;Lamari et al, 1994 (Russo et al, 1988;Collignon et al, 1992) and enhances the biosynthesis and release of both CT and CGRP (Lamari et al, 1994) in CA-77 C cells has already been reported. All-trans-retinoic acid also was shown to decrease both CT and CGRP mRNAs in CA-77 C cells and the secretion of both peptides (Lamari et al, 1994).…”
Section: Discussionmentioning
confidence: 71%
“…Recent evidence suggests that isomerization of all-trans retinoic acid to 9-cis retinoic acid occurs in the cells (Urbach and Rando, 1994). 9-cis retinoic acid, a stereoisomer of all-trans, is a specific ligand for retinoic X receptors (RXR) (Heyman et al, 1992 (Collignon et al, 1992;Lamari et al, 1994). One of the most stricking results was enhancement of the inhibitory effect due to the combined treatment with the calcitriol analogues and 9-cis retinoic acid on the amounts of CGRP and CT, both contained in the C cells and that which was released.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclophilin has been used as an internal standard to quantitate the specificity of changes in calcitonin and calcitonin gene-related peptide mRNA levels in the CA-77 cell line [9], as an internal standard in RT-PCR studies measuring the mRNAs encoding 5-HT1A and 5-HT2A proteins in human hippocampus [3] and as a standard for normalization in experiments examining the effects of steroid hormones and ß-adrenoreceptor agonists on the regulation of the rat Cys S gene [6].…”
Section: Northern Blot Analysesmentioning
confidence: 99%